A Quadruple Integral Involving the Hermite Polynomial Hn(x): Derivation and Evaluation (European Journal of Pure and Applied Mathematics, 2022)
A closed form expression of a quadruple integral involving the Hermite polynomial $H_{n}(x)$ is derived. Special cases are expressed in terms of special functions and fundamental constants. All the results in this work are new.
Keywords: Hermite polynomial; quadruple integral; Hurwitz-Lerch zeta function; Cauchy integral formula